The Effects of Emotional Intelligence on Students' Speaking Skills - Meiva Eka Sri Sulistyawati (EDULANGUE, 2018)
Emotional Intelligence and students’ speaking skills are correlated. This research aims to examine the effects of Emotional Intelligence on students’ speaking skills. The observed population of this research was the XII graders students of the State Senior High Schools in East Jakarta. The sample was taken using simplerandom sampling technique. The data were garnered from questionnaire, objective test, and oral test for both variables. The gained data were then analyzed by using correlation formula and multiple regressions. The empirical evidence showed that there was a significant effect of Emotional Intelligence on the students’speaking skills given the Sig value 0.000 and t observed=4.375. Since Sig value was less than 0.05 and t observed was higher than t-table, it indicated that H0 was rejected, which means that H1 was accepted. It illustrated that there was a significant effect of independent variable X (emotional intelligence) on the dependentvariable Y (student’s speaking skills).